2006
DOI: 10.1159/000093328
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional analysis of human HMBOX1, a homeobox containing protein with transcriptional repressor activity

Abstract: We have identified and isolated a novel human gene, HMBOX1 (homeobox containing 1) from a pancreatic cDNA library. Human HMBOX1 is widely expressed in 18 tissues, and it is highly expressed in pancreas. According to the genome database, HMBOX1 is located at the boundary of 8p12.3 and 8p21.1. HMBOX1 proteins are highly conserved in human, mouse, rat, chicken and Xenopus laevis. A phylogenetic tree shows that HMBOX1 may represent a distinct group in HNF (Hepatocyte Nuclear Factor) transcriptional factors. Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 50 publications
5
45
0
Order By: Relevance
“…Additionally, there was no significant change in hmBOx1 expression in the other cancer tissues tested. Similar to the results reported by chen et al (2), high levels of 3) were pulled down by mab 2a5F4, mab 4a4F2 or the ig isotype antibody, respectively. Complexes and input (non-immunoprecipitated whole cell extract) were detected by Western blot analysis using mAb 4A4F2 or mab 2a5F4 as described in materials and methods.…”
Section: Abnormal Expression Of Hmbox1 In Carcinoma Tissuessupporting
confidence: 88%
See 3 more Smart Citations
“…Additionally, there was no significant change in hmBOx1 expression in the other cancer tissues tested. Similar to the results reported by chen et al (2), high levels of 3) were pulled down by mab 2a5F4, mab 4a4F2 or the ig isotype antibody, respectively. Complexes and input (non-immunoprecipitated whole cell extract) were detected by Western blot analysis using mAb 4A4F2 or mab 2a5F4 as described in materials and methods.…”
Section: Abnormal Expression Of Hmbox1 In Carcinoma Tissuessupporting
confidence: 88%
“…it is a member of the homeobox family of genes, which is characterized by the presence of a dna sequence, the homeobox (1). phylogenetic analyses have confirmed that HMBOX1 is more distantly related to hnF1a and hnF1B and has an atypical homeodomain possessing a 21-amino acid insertion between the second and third helix (2,3). Zhang et al (3) previously cloned a splicing variant of hmBOx1, designated hmBOx1b, from a human pancreatic cdna library.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Human HMBOX1 is widely expressed in at least 18 tissues, and highly in pancreas, brain, placenta, prostate, thymus and testis. Co-transfection of HEK-293T cells with pM-HMBOX1 plasmid and reporter plasmid pGAL4 5 tkLUC indicates that HMBOX1 protein may be one transcription repressor, but how it works is unknown (1).…”
Section: Introductionmentioning
confidence: 99%